ASSESSMENT OF UTILIZATION OF ESSENTIAL IMMUNIZATION SERVICES AMONG CHILDREN UNDER 2 YEARS IN AN URBAN SLUM OF BHUBANESWAR, ODISHA - KUMAR, AMIT; MOHAPATRA, IPSA; MISHRA, KRISHNA (Asian Journal of Pharmaceutical and Clinical Research, 2022)
Objectives: The study was planned with the objectives to assess the under-two immunization coverage and to identify determinants and reasons for non-utilization. Methodology: It was a cross-sectional study which was undertaken in urban slums under field practice area of a medical college, over a span of 4 months among 100 mothers with children 12–23 months of age. Descriptive statistics was used and Fisher’s exact test as the test of association; taking p<0.05 as statistically significant. Results: Mean age of the children was 17.63 months±3.43.72% were fully immunized, 28% partially, and none in unimmunized category. Mother’s literacy status (p=0.03) and father’s literacy status (p=0.0001) were found to be significantly associated with the immunization status of the child. The immunization coverage based on card and history was – BCG (93%), OPV1 (88%), OPV2 (86%), OPV3 (82%), pentavalent 1 (88%), pentavalent 2 (84%), pentavalent 3 (82%), and measles (84%). Waiting time (85.71%) and lack of adequate information (67.86%) were reasons cited for partial immunization. Conclusion: The overall immunization coverage was good with none unimmunized. The literacy status of the parents played a major role in determining the immunization status of the children. Waiting time and lack of information were some of the identified barriers.